Editorial da Revista Contexto Geográfico - Nascimento, Melchior Carlos do; Carvalho, Antonio Alfredo Teles de; Medeiros , Dhiego Antonio de (Revista Contexto Geográfico, 2025)
Editorial Revista Contexto Geográfico v. 10 n. 23, julho de 2025